Review on Unconventional Wind Energy - Gaurav Gulabani; Beegum Shahnaz Abdul Karim; Jayakrishnan Radhakrishnan; Satish Shenoy B; Mohammad Zuber (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Fossil fuel is the major source of energy and is a fast depleting resource. The phenomenal increase in fossil fuel consumption has adversely affected carbon footprint impacting our environment. With strict environmental regulations in place, the focus towards renewable sources of energy is gaining momentum supported by recent advancement in technologies in wind, hydro and solar. Wind turbines were the first forms of clean energy has seen a major increase in power production. The site restrictions, have limited the wind turbine from being used to its maximum potential. In recent years, the concept of some unconventional methods is being proposed. In this review, the various types of wind turbines are emphasized with their recent advances and depicting the challenges faced in various aspects. The reviews contain details mainly about 4 types of wind turbines i.e. floating offshore wind turbine, airborne wind turbine, highway wind turbine systems and locomotive mounted wind turbine.